Sustainability Reporting in Higher Education Institutions: a systematic approach using VOSViewer and Iramuteq softwares - Souza Marins, Bernardo Vitor de; Ferreira, Geraldo de Souza; Ramos, Hellen Costa (International Journal of Advanced Engineering Research and Science, 2021)
There is a lack on the research of sustainability reporting by the higher education institutions, being in its early stages. The paper aims to add to the discussion on sustainability reporting in higher education institutions by identifying which themes are prioritized by authors in this field. The authors conducted systematic review to investigate abstracts using VOSViewer to generate co-authorship networks maps and Iramuteq software to generate Lexicographic analysis, Descending Hierarchical Classification and Correspondence Factor Analysis. Then we analysis the results identifying the main themes addressed by the articles. In this study we covered 50 abstracts from 2016 to 2020 about sustainability reporting in higher education institutions from SCOPUS and Web of Science platforms. The research is limited by the number of publications analyzed, and time frame. In this research, we find that the disclosure of sustainability reporting by HEIs is in its initial stage and diverges in a considerable way from each other. The results may be used by researchers, on account of the key themes presented and by the university's administrative bodies, in order to support the credibility of the sustainability reports published.